Reproducing fear: the effect of birth stories on nulligravid women's birth preferences - Yvette D. Miller; Marion Danoy-Monet (BMC, 2021)
Abstract Objective Preference for caesarean birth is associated with higher fear and lower self-efficacy for vaginal birth. Vicarious experience is a strong factor influencing self-efficacy in nulligravid women, and is increasingly accessible via digital and general media. This study assessed the effect of exposure to different birth stories on nulligravid women's childbirth preferences and the factors mediating these effects. Methods Nulligravid women (N = 426) were randomly allocated to one of four conditions exposing them to written birth stories. Stories varied by type of birth (vaginal/caesarean) and storyteller evaluation (positive/negative) in a 2 × 2 design. Childbirth preference, fear of labour and vaginal birth, and self-efficacy for vaginal birth were measured before and after exposure via a two-way between groups analysis of covariance. Hierarchical regression models were used to determine the mediating effects of change in childbirth fear and childbirth self-efficacy. Results Variations in type of birth and storyteller evaluation significantly influenced childbirth preferences (F (1, 421) = 44.78, p < 0.001). The effect of vaginal birth stories on preference was significantly mediated by fear of labour and vaginal birth and self-efficacy. Effects of exposure to caesarean birth stories were not explained by changes in fear or self-efficacy. Conclusions Childbirth preferences in nulligravid women can be significantly influenced by vicarious experiences. For stories about vaginal birth, the influence of birth stories on women's fear and self-efficacy expectancy are partly responsible for this influence. The findings highlight the importance of monitoring bias in vicarious experiences, and may inform novel strategies to promote healthy childbirth.